The Effect of Watermelon Juice and Cucumber Juice on Blood Pressure Reduction in Elderly People with Hypertension at the Bina Sejahtera Elderly Health Center in Palembang - Anggaraini Anggaraini; Yora Nopriani (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Hypertension is a major degenerative disease, especially among the elderly, and is a leading risk factor for cardiovascular disease and stroke. The World Health Organization defines hypertension as systolic blood pressure ≥140 mmHg and/or diastolic ≥90 mmHg. This study aimed to analyze the effect of watermelon juice and cucumber juice on reducing blood pressure in patients with hypertension. Method: This study used a quantitative quasi-experimental design with a two-group pretest–posttest approach. The research was conducted on January 6, 2025, involving 57 hypertensive patients. Respondents were divided into two intervention groups: watermelon juice and cucumber juice. Blood pressure was measured before and after the intervention. Data were analyzed using univariate and bivariate statistical tests. Results: After watermelon juice administration, most respondents’ systolic blood pressure shifted from stage 2 hypertension to pre-hypertension (60.7%), and diastolic blood pressure also predominantly reached the pre-hypertension category (82.1%). After cucumber juice administration, systolic blood pressure mostly decreased to pre-hypertension (60.7%), and all respondents’ diastolic blood pressure reached the pre-hypertension category (100%). Watermelon juice significantly reduced systolic blood pressure (p = 0.000 < 0.05). Cucumber juice also significantly reduced systolic blood pressure (p = 0.000 < 0.05). There was a significant difference between watermelon and cucumber juice in reducing diastolic blood pressure (p = 0.014 < 0.05). Conclusion: Both watermelon juice and cucumber juice effectively reduce blood pressure in hypertensive patients. However, there is a significant difference between the two interventions in reducing diastolic blood pressure.